The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40429-021-00372-w
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in Treatment Approaches for Addiction — Underlying Mechanisms and Future Directions

Abstract: Purpose of Review While the treatment of addictive disorders proves to be challenging, new treatment approaches that evolved around the concepts of mindfulness and acceptance have been utilized and investigated in recent years. Our goal is to summarize the efficacy and possible underlying mechanisms of mindfulness-based interventions (MBI) in addictive disorders. Recent Findings Various meta-analyses have suggested that MBIs show clinical efficacy in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 104 publications
4
27
0
Order By: Relevance
“…However, mind wandering did not have a direct mediating role. Several studies have shown that mind wandering has a close relationship with boredom (28), and its causative effect has even been examined ( 29); therefore, it can be concluded that although mind wandering cannot directly play a mediating role between evolutionary fitness and addiction potential, in line with previous studies, it can increase boredom (30) which will eventually increase one's addiction potential.…”
Section: Discussionsupporting
confidence: 64%
“…However, mind wandering did not have a direct mediating role. Several studies have shown that mind wandering has a close relationship with boredom (28), and its causative effect has even been examined ( 29); therefore, it can be concluded that although mind wandering cannot directly play a mediating role between evolutionary fitness and addiction potential, in line with previous studies, it can increase boredom (30) which will eventually increase one's addiction potential.…”
Section: Discussionsupporting
confidence: 64%
“…Mindfulness is a state of consciousness produced by purposeful and non-judgmental attention to the present; it focuses on learning in the face of depression and negative thinking, and emphasizes the conscious need to point to current experiences and maintain an open, curious, and receptive attitude ( Bishop et al, 2004 ). Mindfulness can effectively improve the symptoms of internet addiction ( Rosenthal et al, 2021 ), and this improvement is long-term ( Calvete et al, 2017 ). Therefore, mindfulness therapy can be used to improve poor cognitive strategies and to treat internet addiction effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this article was to systematically review and evaluate the evidence base on several mindfulness-based and neurofeedback interventions in the specific context of cognitive and affective processes involved in disorders due to nonsubstance addictive behaviors. This aim discriminates this systematic review from existing reviews that addressed mindfulness techniques among addiction in general (e.g., Rosenthal et al, 2021), focused on one specific behavioral addiction (e.g., de Lisle et al, 2011), or evaluated generic health outcomes rather than addiction-specific processes (e.g., Sancho et al, 2018). Specific research questions addressed (a) the nature of mindfulness and neurofeedback techniques, (b) the effectiveness of these techniques in influencing addiction-related affective and cognitive mechanisms (i.e., stress responsiveness, craving, inhibitory control, decision-making, and cognitive biases; see Figure 1), and (c) effects of these techniques on symptom severity in the realm of gaming disorder, gambling disorder, problematic use of social media, problematic pornography use and other compulsive sexual behaviors, and problematic buying-shopping.…”
mentioning
confidence: 99%